Catalysis of ACAT may be completed within the plane of the membrane: a working hypothesis - Ta Yuan Chang; Catherine C.Y. Chang; Xiaohui Lu; Song Lin (Journal of Lipid Research, 2001)
Two ACAT sharing protein sequence homology near their C termini have been identified. Both proteins may span the endoplasmic reticulum (ER) membrane several times. There is good evidence implicating the role of ACAT1 in macrophage foam cell formation, and ACAT2 in intestinal cholesterol absorption. On the other hand, the functional roles of ACAT1 and ACAT2 in the VLDL or chylomicron assembly process are less clear. It is possible that both enzymes are able to form lipid droplets (which are present in the cytoplasm), and participate in lipoprotein assembly (which occurs in the ER lumen). To link the site of ACAT catalysis with its function, we propose that part of the ACAT catalytic site may reside within the lipid bilayer, allowing catalysis to be completed within the plane of the membrane. Cholesteryl esters (CE) produced in situ may burst into cytoplasmic lipid droplets, carrying phospholipid monolayers as their outer coats. In cells engaged in lipoprotein assembly and secretion, CE in the bilayer may be recognized by the specific protein microsomal triacylglycerol transfer protein (MTP), reaching out from the lumenal side of the membrane. MTP then lipidates the growing apolipoprotein B (apoB) chain with CE and TG during the early stages of apoB lipoprotein assembly.—Chang, T. Y., C. C. Y. Chang, X. Lu, and S. Lin. Catalysis of ACAT may be completed within the plane of the membrane: a working hypothesis. J. Lipid Res. 2001. 42: 1933–1938.